THE EFFECTS OF N?-NITRO-L-ARGININE (L-NNA) ON BLOD PRESSURE AND SURVIVAL OF THE SKIN FLAPS IN RATS - Kose, Rustu; Yildirim, A. Mustafa; Okur, M. Ihsan; Tugrul, Ibrahim (Medknow Publications & Media Pvt Ltd, 2010)
Object: This study in planned to investigate the effect of N-omega-nitro-L-arginin (L-NNA), which is nitric oxide synthase inhibitor, on the blood pressure and survival of the skin flap of rats. Material and Methods: 16 Wistar albino male rats are used in the study. They were divided into 2 groups, each containing 8 rats. In the control group, tap water was given for 3 weeks. In group L-NNA, 50mg/350ml/day L-NNA was administered with tap water for 3 weeks. Blood pressure was measured by indirect tail cuff method during the conscious period. Cranial based random flaps 8x3 cm in size were raised from dorsal skin of the rats at the 14th day of the study. Fluorescein sodium solution (0.5 ml) administered intraperitoneally at the 21st day. The viable and the necrotic parts of the flaps were labeled on the clear acetate sheets. The viable parts on the sheets were calculated by digital planometry. Results: The arterial blood pressure of the rats which were administered 21 mg/kg/day L-NNA for 21 day was increased however; the effect on the flap survival was statistically insignificant.